Persoalan Aksiologi dakwah dan penerapannya di bidang Keilmuan - Novri Hardian; Neneng Hastuti (Al-Hikmah: Jurnal Dakwah dan Ilmu Komunikasi, 2019)
The wisdom of da'wah is increasingly developing along with the development of scientific studies of da'wah. strategies and steps are needed to finish explaining the da'wah study because of the many interpretations of da'wah knowledge. This research methodology uses random sampling as well as interviews with lecturers and students about the science of da'wah. hence from this article it is expected to provide a review and explanation of where the science of da'wah and its expectations are in the middle of the Islamic campus, how important is the axiology in the study so that it can have the aesthetics and values of each quality science